The effectiveness of the Mining Qualifications Authority’s monitoring and evaluation system - Gamakulu, Sitembiso (My University, 2016)
The South African Government set up the Mining Qualifications Authority (MQA) in 1996 under the Mine Health and Safety Act, 29 of 1996 to train mineworkers on health and safety issues to minimise injuries and deaths. Later the then Minister of labour reestablished the Authority as a Sector Education and Training Authority (SETA) in 2000 when SETAs were set up to replace the old Industry Training Boards (ITBs) (Skills Development Act, 97 of 1998). The mandate of SETAs includes providing for learnerships, internships, undergraduate bursaries, graduate development programmes, and apprenticeships. These Authorities have several challenges. These include poor governance, lack of accountability, Lack of and poor quality data, inadequate information management, and absent or ineffective monitoring and evaluation arrangements (Ministerial Task Team on Performance of SETAs, 2013). These challenges have not spared the MQA and has led to declining performance for two consecutive financial years; namely, 2012-2013 and 2013-2014 (MQA Annual Reports, 2012-2013 and 2013-2014. However, only effective monitoring and evaluation arrangements can track and assess reliably how the Authority is performing and why. Therefore, we need to examine the Authority’s monitoring and evaluation system. To undertake this examination, the study posed two questions. To understand our research context, we reviewed literature relating to the history and description of the Authority and the establishment of the SETAs in general. We further undertook a research problem analysis to understand the history and description of monitoring and evaluation in the South African public sector. To do this, we reviewed briefly monitoring and evaluation systems of other developed and developing countries globally. From the reviewed literature, we developed a conceptual framework to guide our research in collecting, processing, and analysing of results. Relatedly, we developed an explanatory framework that helped us in interpreting our findings. Some of our findings pointed to the weaknesses of the MQA’s monitoring and evaluation system in such areas of monitoring and evaluation organisational capacity and documented monitoring and evaluation reporting processes and system. We concluded by providing some recommendations to strengthen the MQA’s monitoring and evaluation system
Thesis presented in partial fulfilment for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, 2016
Keywords: South Africa--Mining Qualifications Authority; Mining schools and education--South Africa; Mineral industries--South Africa